Detecting Specialization in Offending: Comparing Analytic Approaches - Sullivan, Christopher J. (Journal of quantitative criminology, 2009)
Offending specialization continues to be a subject of empirical inquiry for scholars interested in criminal careers. Early research consistently spoke to the generality of offending profiles, but more recent work has revealed somewhat mixed findings. These results have emerged alongside newly developed and applied methods that detect and describe offending specialization. To what extent these methods shape divergent conclusions and/or provide overlapping insight remains unclear, however. Therefore, the degree to which more recent inquiries are actually studying the same operational definition of specialization is unknown. In order to consider this issue further, this study utilizes four frequently applied approaches with a single data set. The study indicates when and where findings converge and also describes any unique insights provided by each method. The work concludes with a discussion surrounding the utility of applying multiple strategies in assessing specialization in criminal offending.